Far out fables. Punk rock mouse and country mouse : a graphic novel - Terrell, Brandon, 1978-2021 (Stone Arch Books, 2021)
A punk rock mouse and a country signing mouse are envious of each other's lives, but when they magically switch places they learn things may seem more appealing than they actually are. Includes a classic retelling of the fable, visual questions, and a glossary.